2022
DOI: 10.1002/zaac.202100329
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adsorption and selective capture of methylene blue by anionic In‐based MOF with carboxyl‐decorated pore surface

Abstract: We reported a PtS-type anionic metal organic framework (MOF) with uncoordinated carboxyl-groups and suitable pore size, (InOF). InOF displays highdensity electronegative functional sites about 12 negative sites in one unit cell, which exhibits its potential application for selective removal cationic dye from effluents. In fact, the InOF crystals can rapidly and selectively capture methylene blue dyes from effluents based on the charge-effect and size-effect at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…While the MB + and BG + display just about 54.0% and 56.3%, removal efficiency after 25 min and 20 min, respectively. In addition, the removal efficiency of HDU-1 for MB and BG molecules is also comparable to those research in reported MOFs NOTT-210 [38], InOF [36], ZJU-24-0.89 [39], Cu 2 (L)(H 2 O) 2 [40], and JOU-11 [20]. These results indicated that HDU-1 has different adsorption rate VB + > BG + > MB + > RhB + > R6G + for the cationic organic dyes with different size and shape.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While the MB + and BG + display just about 54.0% and 56.3%, removal efficiency after 25 min and 20 min, respectively. In addition, the removal efficiency of HDU-1 for MB and BG molecules is also comparable to those research in reported MOFs NOTT-210 [38], InOF [36], ZJU-24-0.89 [39], Cu 2 (L)(H 2 O) 2 [40], and JOU-11 [20]. These results indicated that HDU-1 has different adsorption rate VB + > BG + > MB + > RhB + > R6G + for the cationic organic dyes with different size and shape.…”
Section: Resultssupporting
confidence: 86%
“…Aside from the metal clusters with an electric charge in MOFs, some organic ligands can also further provide a negative charge due to uncoordinated carboxyl groups or exposed functional groups, such as -COOH, -OH, imide groups. These functional groups can also enhance the interaction with dye molecules through hydrogen bonding, electrostatic interactions, and π-π stacking interactions [ 35 , 36 , 37 ]. Therefore, anion frameworks constructed via In(III) ions with linkers modified by functional groups conducive to efficiently and rapidly capture organic dyes from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%